Evaluation of Energy Efficiency and Illuminance Performance of LED Lighting Systems in Office Spaces Using DIALux Simulation - Aat Januar Habibi; Erfiana Wahyuningsih (International Journal Science and Technology, 2026)
Energy efficiency in office buildings has become a critical issue due to increasing electricity consumption, particularly in lighting systems that operate continuously. Inefficient lighting design can lead to excessive energy use, higher operational costs, and reduced sustainability performance in commercial buildings. Objective: This study aims to analyze the implementation of Light Emitting Diode (LED) technology to improve energy efficiency in office lighting systems using DIALux simulation, while ensuring compliance with standard illumination requirements. Method: This research employs a quantitative descriptive approach supported by simulation modeling. Data were collected through field observation, illumination measurement using a lux meter, and documentation of room specifications. The analysis was conducted using DIALux software to evaluate illuminance levels, light distribution, and energy consumption based on office lighting standards. Findings: The results indicate that the LED lighting system achieves an average illuminance of 340 lux, which meets the SNI 6197:2011 standard (300–500 lux), with a uniformity ratio of 0.68 indicating adequate light distribution and visual comfort. The system consumes 36 kWh per month, which is more than 50% lower than conventional fluorescent (TL) lighting systems. Implications: The findings suggest that LED lighting systems can provide efficient and compliant lighting solutions while significantly reducing energy consumption and operational costs. This supports the implementation of energy-efficient and sustainable building practices. Originality: The originality of this study lies in its integrated approach that combines room characteristics, LED configuration, and DIALux simulation to evaluate lighting performance and energy efficiency simultaneously, offering a practical framework for office lighting design.